Analisis Sentimen Tanggapan Masyarakat Aplikasi Tiktok Menggunakan Metode Naive Bayes dan Categorial Propotional Difference (CPD) - Junda Alfiah Zulqornain; Indriati Indriati; Putra Pandu Adikara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
The TikTok application is a social media that is currently often discussed among the public. Starting from the young to the old using this TikTok application. The TikTok application is an application that can share videos, but usually videos that have vulgar elements can be seen by minors because the TikTok application does not start from age. Therefore the authors conducted a sentiment analysis on the TikTok application reviews to help parents in selecting applications for their children. From these problems the authors conducted a sentiment analysis using the Naive Bayes method and the Categorial Propotional Difference. Research testing using 5-Cross Validation with a variation of the terms used. The maximum results obtained using the term 100% are used for testing with an accuracy of 0,729947, a precission value of 0,746854, a recall value of 0,926118, and an f-measure value of 0,824511.